2018
DOI: 10.2147/vhrm.s176167
|View full text |Cite
|
Sign up to set email alerts
|

Noncardiac Lebanese hospitalized adult patients’ awareness of their coronary artery disease risk factors

Abstract: BackgroundNoncommunicable diseases are the leading cause of death in Lebanon, with cardiovascular diseases accounting for almost half of the annual deaths.PurposeWe aimed to determine awareness of noncardiac Lebanese hospitalized patients for their coronary artery disease risk factors, their level of adherence to medications or lifestyle modifications, and assess factors associated with awareness.Materials and methodsA cross-sectional study was conducted in 14 hospitals with a total of 382 patients. Levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 23 publications
5
7
0
Order By: Relevance
“…In the present study, we found that 58.6% of the participants had a BMI of ≥25 kg/m 2 . Our BMI results are consistent with the previous study of Saudi Arabia [ 37 ] but lower than Oman [ 25 ] and Lebanon [ 38 ] and higher than the Cameroon population. [ 26 ] BMI has been significantly high in urban, older age, women, and lower educational level participants compared to their counterparts.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, we found that 58.6% of the participants had a BMI of ≥25 kg/m 2 . Our BMI results are consistent with the previous study of Saudi Arabia [ 37 ] but lower than Oman [ 25 ] and Lebanon [ 38 ] and higher than the Cameroon population. [ 26 ] BMI has been significantly high in urban, older age, women, and lower educational level participants compared to their counterparts.…”
Section: Discussionsupporting
confidence: 93%
“…These ndings on the levels of adherence among our sample are similar to the ndings reported by studies conducted in other Eastern countries [24,25,26]. For example, Ghaddar and colleagues [25] reported that patients with CAD had low adherence to physical activity (10.8% − 14.7%) and weight loss (33.3% − 61.3%) but had satisfactory adherence to taking medications (83% − 89.9%). On the contrary, high adherence rates to healthy lifestyle behaviors have been reported by studies conducted in Western countries.…”
Section: Discussionsupporting
confidence: 90%
“…Epidemiological studies have shown that among the risk factors of coronary artery disease (CAD), cerebral infarction, including other cardiovascular and cerebrovascular diseases, dyslipidemia is an important factor [1,2,3]. The characteristics of dyslipidemia are very complex, mainly due to genetic or environmental factors [4], as well as their interaction [5].…”
Section: Introductionmentioning
confidence: 99%